What matters to students’ success in mathematics? The case of fractions - Winsløw, Carl (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2019)
Fractions are at the transition between everyday arithmetic and algebra, and there is hardly any domain of mathematics – not least when it comes to applied mathematics – where fractions do not appear. What is actual the significance of this subject in elementary education and beyond? In what sense are teachers a key to students’ learning in this area? What must teachers in elementary school know about it? What systemic conditions are important or even necessary to teachers’ and students’ success in teaching and learning fractions? What kind of research can enlighten us on these matters?